Effectiveness of a resilience school-based intervention in adolescents at risk: a cluster-randomized controlled trial - Llistosella, Maria; Castellví, Pere; García-Ortiz, Mercedes; López-Hita, Griselda; Torné, Clara; Ortiz, Ramona; Guallart, Erika; Uña-Solbas, Estefanía; Carlos Martín-Sánchez, Juan (Frontiers in Psychology, 2024)
Introduction: School offers a key context to promote resilience. The aim of this study was to assess the effectiveness of a school-based resilience intervention in 578 at-risk adolescents aged 12 to 15, emphasizing the significance of resilience in improving mental. Methods: A cluster-randomized controlled trial with parallel arms was conducted during the 2021/22 academic course. Primary outcomes were assessed by the Child Youth Resilience Measure-32 at baseline (T1), post-intervention (T2), and then at the 24-week follow-up (T3). Both groups were compared using the Student's t-test. The effect size was calculated using Cohen's d and linear regression models were used.Results: A total of 578 adolescents were included, 323 in the control group and 255 in the intervention group. Significant differences in both crude and adjusted analyses for Child Youth Resilience Measure were observed, showing higher resilience for the intervention group [(IG, M = 128.7, SD = 14.2; CG, M = 125.3, SD = 18.4; p = 0.027; d = 0.2; p = 0.043, d= 0.16]. Furthermore, in Depressive symptoms, lower values were found for the intervention group in both crude and adjusted analyses [(IG, M = 2.3 (SD= 2.5); CG, M= 2.8 (SD=2.5); p = 0.04; d=-0.20; p=0.037, d= -0.18].Discussion: This study contributes to fostering resilience and positive adolescent development. It also reinforces the potential of multicomponent interventions. More continuous follow-up assessments are needed to identify possible long-term changes in resilience.